Highly efficient synergistic activity of an α-L-arabinofuranosidase for degradation of arabinoxylan in barley/wheat - Wen, Jiaqi; Miao, Ting; Basit, Abdul; Li, Qunhong; Tan, Shenglin; Chen, Shuqing; Ablimit, Nuraliya; Wang, Hui; Wang, Yan; Zheng, Fengzhen; Jiang, Wei (Frontiers in Microbiology, 2023)
Here an α-L-arabinofuranosidase (termed TtAbf62) from Thermothelomyces thermophilus is described, which efficiently removes arabinofuranosyl side chains and facilitates arabinoxylan digestion. Specific activity of TtAbf62 (179.07 U/mg) toward wheat arabinoxylan was the highest among all characterized glycoside hydrolase family 62 enzymes. TtAbf62 in combination with endoxylanase and β-xylosidase strongly promoted hydrolysis of barley and wheat. Release of reducing sugars was significantly higher for the three-enzyme combination relative to the sum of single-enzyme treatments: 85.71% for barley hydrolysis and 33.33% for wheat hydrolysis. HPLC analysis showed that TtAbf62 acted selectively on monosubstituted (C-2 or C-3) xylopyranosyl residues rather than double substituted residues. Site-directed mutagenesis and interactional analyses of enzyme-substrate binding structures revealed the catalytic sites of TtAbf62 formed different polysaccharide-catalytic binding modes with arabinoxylo-oligosaccharides. Our findings demonstrate a “multienzyme cocktail” formed by TtAbf62 with other hydrolases strongly improves efficiency of hemicellulose conversion and increases biomass hydrolysis through synergistic interaction.